Assessment of Collagen-Induced Arthritis Using Cyanine 5.5 Conjugated with Hydrophobically Modified Glycol Chitosan Nanoparticles: Correlation with F-18-Fluorodeoxyglucose Positron Emission Tomography Data - Cha, Ji Hyeon; Lee, Sang Hoon; Lee, Sheen-Woo; Park, Kyeongsoon; Moon, Dae Hyuk; Kim, Kwangmeyung; Biswal, Sandip (KOREAN RADIOLOGICAL SOC, 2012)
Objective: To evaluate the potential and correlation between near-infrared fluorescence (NIRF) imaging using cyanine 5.5 conjugated with hydrophobically modified glycol chitosan nanoparticles (HGC-Cy5.5) and F-18-fluorodeoxyglucose-positron emission tomography (F-18-FDG-PET) imaging of collagen-induced arthritis (CIA). Materials and Methods: We used 10 CIA and 3 normal mice. Nine days after the injecting collagen twice, microPET imaging was performed 40 minutes after the intravenous injection of 9.3 MBq F-18-FDG in 200 mu L PBS. One day later, NIRF imaging was performed two hours after the intravenous injection of HGC-cy5.5 (5 mg/kg). We assessed the correlation between these two modalities in the knees and ankles of CIA mice. Results: The mean standardized uptake values of F-18-FDG for knees and ankles were 1.68 +/- 0.76 and 0.79 +/- 0.71, respectively, for CIA mice; and 0.57 +/- 0.17 and 0.54 +/- 0.20 respectively for control mice. From the NIRF images, the total photon counts per 30 mm(2) for knees and ankles were 2.32 +/- 1.54 x 10(5) and 2.75 +/- 1.51 x 10(5), respectively, for CIA mice, and 1.22 +/- 0.27 x 10(5) and 0.88 +/- 0.24 x 10(5), respectively, for control mice. These two modalities showed a moderate correlation for knees (r = 0.604, p = 0.005) and ankles (r = 0.464, p = 0.039). Moreover, both HGC-Cy5.5 (p = 0.002) and F-18-FDG-PET (p = 0.005) imaging also showed statistically significant differences between CIA and normal mice. Conclusion: NIRF imaging using HGC-Cy5.5 was moderately correlated with F-18-FDG-PET imaging in the CIA model. As such, HGC-Cy5.5 imaging can be used for the early detection of rheumatoid arthritis.
Keywords: NEAR-INFRARED FLUORESCENCE; RHEUMATOID-ARTHRITIS; DISEASE-ACTIVITY; F-18-FDG PET; BLOOD-FLOW; MODEL; PATHOGENESIS; LIPOSOMES; ANTIBODY; DYES